PENGARUH ANGGARAN PARTISIPATIF DAN KAPASITAS INDIVIDU TERHADAP SENJANGAN ANGGARAN DAN KINERJA APARATUR PEMERINTAH (STUDI EMPIRIS PADA PEMERINTAH PROPINSI JAWA TIMUR) - Hendra Yuniarno Saputra; Bambang Subroto; Abdul Ghofar (Universitas Negeri Malang, 2017)
This study reviews the direct influence of participatory budgeting and individual capacity on budgetary slack and the performance of government officials. Further, it also reviews the role of budgetary slack in mediating participatory budgeting and capacity of individual on the performance of government officials. The sample of this study is 111 department head in the provincial government of East Java. The results show that the performance of government officials increases/decreases due to participatory budgeting and individual capacity. In addition, this study identifies that budgetary slack increases/decreases because of participatory budget. However, it does not find the mediating role of budgetary slack in the relation between participatory budget and capacity of individual on the performance of government officials.Keywords: The performance of government officials, budgetary slack, intervening, SEM-PLS